BHIVA position statement on HIV, the law and the work of the clinical team. (December 2022) - Saigal, Priyanka; Phillips, Matt; Bernard, Edwin; Douglas, Calum; Poulton, Mary; Smithson, Kat; Sparrowhawk, Alex; Ward, Chris; Weait, Matthew
The purpose of this statement is to outline issues at the interface between HIV transmission and the law and provide guidance to healthcare professionals (HCPs) working in the field of HIV medicine. The guidance is to support work in the UK, and it is important to note that the law in England and Wales differs from that in Scotland and Northern Ireland. Approaches are suggested to deal with these issues consistently, within legal and General Medical Council (GMC) regulatory frameworks and in the context of the public health agenda. The guidance specifically addresses sexual transmission.